Analysis of the water quality index of the Escalera river applying the ICA-PE methodology in the periods 2015-2018 - Alvarez Ticllasuca, Adiel (2021)
The objective of the research was to apply the methodology for the determination of the ICA-PE water quality index in the Escalera river of the Huachocolpa district in the periods of 2015 and 2018, the samplings carried out were given 2 points (REsca1 and REsca2), For data collection, it was based on mathematical simulation, documentary analysis and registration, at the sampling points the concentrations of aluminum, arsenic, cadmium, copper, iron, manganese, lead and zinc were determined, these parameters exceeded the environmental quality standards. Water (ECA-AGUA) was later categorized according to the ICA-PE water quality index, of which for 2015 it was of good quality obtaining a value of 73.14 and for 2018 its quality decreased to regular reaching a value of 61.85 . The results obtained show that the quality of water is decreasing in its path that runs through the Escalera river, due to the different anthropogenic activities that take place around it, altering its quality and reducing its capacity for self-purification.